The Attitude Towards The Practice of Physical Education and Sports and its Relationship to Self-Esteem Among Secondary School Students - Boudjellal, Souhila; Ben Amour, Djamila (sports creativity, 2025)
The present study aimes to identify the relationship between the attitude towards the practice of physical education and sports and self-esteem among secondary school students. The relational descriptive approach was used, and a questionnaire of attitude towards the practice of physical education and sports prepared by Ismail Marwa was applied, and the Self-Esteem Scale of Cooper Smith on a sample consisting of (102) students from some secondary schools in M'sila. The results showed the existence of positive attitudes towards practice of physical education and sports , and high level of self-esteem, in addition of statisticaly significant correlation between the attitude towards practice of physical education and sports and self-esteem among secondary school students .